PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN TAPANULI TENGAH - Yessi Mayasari; Rudi Alam Gaus; Saipudin Sefa; Salpila Dewi; Siti Rakhmawati (Manajemen dan Bisnis, 2022)
This formula research internal issue is how influence of work environment on employees performance. How influence job motivation on employees performance. How influence of leadership style on employees performance. How influence of work environment, job motivation, and leadership style on employees performance. This research target is to for know influence and analyze work environment on employees performance. For know influence and analyze job motion employees performance. For know influence and analyze leadership style on employees performance. For know influence and analyze work environment, job motivation, and leadership style on employees performance Sample in this research amount to 39 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of work environment effect positive and significant on employees performance. Job motivation effect positive and don’t significant on employees performance. Leadership style effect positive and significant on employees performance. Work environment, job motivation and leadership style effect and positive and significant on employees performance